Temporal trends of persistent organic pollutants in Barents Sea polar bears (Ursus maritimus) in relation to changes in feeding habits and body condition - Lippold, Anna; Bourgeon, Sophie; Aars, Jon; Andersen, Magnus; Polder, Anuschka; Lyche, Jan Ludvig; Bytingsvik, Jenny; Jenssen, Bjørn Munro; Derocher, Andrew E.; Welker, Jeffrey Martin; Routti, Heli (Environmental Science & Technology, 2018)
Temporal trends of persistent organic pollutants (POPs: PCBs, OH-PCBs, p,p′ -DDE, HCB, β-HCH, oxychlordane, BDE-47, and 153) in relation to changes in feeding habits and body condition in adult female polar bears ( Ursus maritimus ) from the Barents Sea subpopulation were examined over 20 years (1997–2017). All 306 samples were collected in the spring (April). Both stable isotope values of nitrogen (δ 15 N) and carbon (δ 13 C) from red blood cells declined over time, with a steeper trend for δ 13 C between 2012 and 2017, indicating a decreasing intake of marine and high trophic level prey items. Body condition, based on morphometric measurements, had a nonsignificant decreasing tendency between 1997 and 2005, and increased significantly between 2005 and 2017. Plasma concentrations of BDE-153 and β-HCH did not significantly change over time, whereas concentrations of Σ4PCB, Σ5OH-PCB, BDE-47, and oxychlordane declined linearly. Concentrations of p,p′ -DDE and HCB, however, declined until 2012 and 2009, respectively, and increased thereafter. Changes in feeding habits and body condition did not significantly affect POP trends. The study indicates that changes in diet and body condition were not the primary driver of POPs in polar bears, but were controlled in large part by primary and/or secondary emissions of POPs.